Mass‐transfer rate enhancement for CO2 separation by ionic liquids: Theoretical study on the mechanism. Issue 12 (19th August 2015) - Xie, Wenlong; Ji, Xiaoyan; Feng, Xin; Lu, Xiaohua
Abstract : To promote the development of ionic liquid (IL) immobilized sorbents and supported IL membranes (SILMs) for CO2 separation, the kinetics of CO2 absorption/desorption in IL immobilized sorbents was studied using a novel method based on nonequilibrium thermodynamics. It shows that the apparent chemical‐potential‐based mass‐transfer coefficients of CO2 were in three regions with three‐order difference in magnitude for the IL‐film thicknesses in microscale, 100 nm‐scale, and 10 nm‐scale. Using a diffusion‐reaction theory, it is found that by tailoring the IL‐film thickness from microscale to nanoscale, the process was altered from diffusion‐control to reaction‐control, revealing the inherent mechanism for the dramatic rate enhancement. The extension to SILMs shows that the significant improvement of CO2 flux can be obtained theoretically for the membranes with nanoscale IL‐films, which makes it feasible to implement CO2 separation by ILs with low investment cost. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4437–4444, 2015